1976
DOI: 10.1093/ajcn/29.8.859
|View full text |Cite
|
Sign up to set email alerts
|

Food iron absorption in human subjects. III. Comparison of the effect of animal proteins on nonheme iron absorption

Abstract: The ability of various animal proteins to enhance the absorption of dietary nonheme iron was evaluated by performing multiple radioiron absorption measurements in 70 volunteer subjects. Protein equivalent substitutions of nine animal foods were made in two basic test meals. The first was a standard meal of high iron availability (mean absorption, 8.3%) containing beef muscle as the animal protein. The second was a semisynthetic meal of low iron availability (mean absorption, 1.4%) containing ovalbumin as the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
136
1
2

Year Published

1980
1980
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(142 citation statements)
references
References 18 publications
3
136
1
2
Order By: Relevance
“…The present study indicates that beef enhances Fe uptake 2 -3-fold, a magnitude similar to that reported in human subjects (1) and cell-culture studies (20) .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The present study indicates that beef enhances Fe uptake 2 -3-fold, a magnitude similar to that reported in human subjects (1) and cell-culture studies (20) .…”
Section: Discussionsupporting
confidence: 89%
“…Beef and GLM digestates both significantly enhanced Fe absorption compared with egg albumin. In conclusion, GLM digestate significantly enhances non-haem Fe uptake in Caco-2 cells with a similar magnitude to that of beef.Key words: Iron absorption: Mussels: Caco-2: Meat factor Red meat, pork, poultry and fish all significantly enhance Fe absorption when consumed as part of a vegetable-based meal in human subjects (1) . Further investigation into the bioactive components of meat, poultry and fish factor suggests that cysteine-rich myofibrils (2) , glycosaminoglycans (3) and L-a-glycerophosphocholine (4) could be responsible for this enhancing effect, either individually or in combination (5) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, enhancers as well as inhibitors of absorption influence to a larger extent the non-haem iron whose absorption is between 2 and 20% (Hallberg, 1981). Dependence on plant based foods for iron nutrition may thus result into a high prevalence of iron deficiency, particularly in populations that are at risk like children and pregnant women who have higher needs (Cook et al, 1976;Yip 1988). There is therefore a need in understanding how dietary factors, including iron availability and intake, influence iron status.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that many forms of iron do not enter the iron common pool and remain unavailable for absorption. Secondly, soy protein [28] and milk proteins [29,30] have been associated with lower iron bioavailability even in the absence of phytic acid, but from these results, it appears that soy protein in SPC played a more significant role than milk proteins in DSMP to and further reduced iron bioavailability in SPC recipe. For adequate bioavailability of iron, the PA/Fe molar ratio should be <1 [30].…”
Section: Resultsmentioning
confidence: 96%